Invasive pneumococcal diseases in children and adults before and after introduction of the 10-valent pneumococcal conjugate vaccine into the Austrian national immunization program - Richter, Lukas (PLoS One, 2019)
BACKGROUND: In February 2012 the ten-valent pneumococcal conjugate vaccine (PCV10) with a 2+1 doses schedule (3, 5, 12 or 14 months of age) without catch-up vaccination was introduced in Austria. We assessed direct and indirect vaccine effects on invasive pneumococcal disease (IPD) by a population-based intervention study. METHODS: The study period was divided into pre- (2009–2011) and post-period (2013–2017, February), regarding 2012 as transition year. Outcomes were defined as PCV10 ST-IPD, the PCV10-related ST 6A and 19A IPD and non-PCV10 excluding ST 6A-/19A-IPD (NVT-IPD). We used national surveillance data and compared average monthly incidence rate (IR) between pre- and post-period among <5, 5–49 and ≥50 years old. Additionally, for the 5–49 and ≥50 years old, and the 50–59 and ≥60 years old, we analyzed monthly incidence data of the pre-, post-period, and estimated trend and level changes by using a segmented time-series regression. RESULTS: The PCV-10 IPD was reduced by 58% (95% CI: 30%; 74%) and 67% (95% CI: 32%; 84%) among <5 and ≥50 years old; the reduction in ≥60 years was 71% (95% CI: 36%; 88%). There were no significant changes in the pre-post-rate or incidence trend of NVT-IPD in the <5 and ≥50 years old. ST-specific analyses revealed no ST 6A- and ST 19A IPD decline in any age-group, and a ST 8 IPD increase among ≥50 years old (IR ratio: 3.5; 95% CI: 1.7; 7.2). We found no vaccine effects among 5–49 years old. CONCLUSIONS: Our study adds to the evidence on direct and indirect protection of a childhood PCV10 vaccine program. Elderlies seem to benefit the most. Findings did not support PCV 10 cross-protection, but indicate replacement at least for ST 8 among the ≥50 years old. Follow-up analyses of IPD surveillance data are needed to fully characterize the magnitude of serotype replacement and further vaccine-attributable IPD reduction with time.